mRNA-1273 or mRNA-Omicron boost in vaccinated macaques elicits similar B cell expansion, neutralizing responses, and protection from Omicron - Gagne, Matthew; Moliva, Juan I.; Foulds, Kathryn E.; Andrew, Shayne F.; Flynn, Barbara J.; Werner, Anne P.; Wagner, Danielle A.; Teng, I-Ting; Lin, Bob C.; Moore, Christopher; Jean-Baptiste, Nazaire; Carroll, Robin; et al. (Cell, 2022)
SARS-CoV-2 Omicron is highly transmissible and has substantial resistance to neutralization following immunization with ancestral spike-matched vaccines. It is unclear whether boosting with Omicron-matched vaccines would enhance protection. Here, nonhuman primates that received mRNA-1273 at weeks 0 and 4 were boosted at week 41 with mRNA-1273 or mRNA-Omicron. Neutralizing titers against D614G were 4,760 and 270 reciprocal ID50 at week 6 (peak) and week 41 (preboost), respectively, and 320 and 110 for Omicron. 2 weeks after the boost, titers against D614G and Omicron increased to 5,360 and 2,980 for mRNA-1273 boost and 2,670 and 1,930 for mRNA-Omicron, respectively. Similar increases against BA.2 were observed. Following either boost, 70%–80% of spike-specific B cells were cross-reactive against WA1 and Omicron. Equivalent control of virus replication in lower airways was observed following Omicron challenge 1 month after either boost. These data show that mRNA-1273 and mRNA-Omicron elicit comparable immunity and protection shortly after the boost. [Display omitted] •mRNA-1273 prime induces cross-reactive B cells to Omicron and ancestral strains•Boosting with mRNA-1273 or mRNA-Omicron enhances neutralization of Omicron•Either boost expands B cells cross-reactive to Omicron and ancestral strains•mRNA-1273 or mRNA-Omicron boost is protective against Omicron replication in the lungs Boosting previously vaccinated nonhuman primates with either the mRNA-1273 or mRNA-Omicron vaccine expands cross-reactive memory B cells and elicits similar levels of protection upon challenge with SARS-CoV-2 Omicron.